Entrenamiento visual en niños con baja visión” (2021)
Early visual stimulation is the set of special educational programs that involve ordered visual experiences and according to the child's age, it must be done in stages early to take advantage of brain plasticity that allows the acquisition of basic functions; in children with low vision, early stimulation becomes a stimulation strategy which, when carried out at the right time, seeks to make the most of the vision residual. The lack of deepening and dissemination of the subject means that many health professionals do not know the importance of visual stimulation and the advantages of performing it in stages early in the child, for this reason a review of the subject was carried out to determine the function of the Early visual stimulation in children with low vision.